2007
DOI: 10.1186/1471-2474-8-98
|View full text |Cite
|
Sign up to set email alerts
|

Locally applied Simvastatin improves fracture healing in mice

Abstract: Background: HMG-CoA reductase inhibitors, statins, are widely prescribed to lower cholesterol. High doses of orally administered simvastatin has previously been shown to improve fracture healing in a mouse femur fracture model. In this study, simvastatin was administered either subcutaneously or directly to the fracture area, with the goal of stimulating fracture repair at acceptable doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1
8

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 30 publications
4
40
1
8
Order By: Relevance
“…Consequently, studies on topical application of statins have been performed. These studies are consistent and report likewise improved fracture healing in rodents treated with statins topically (Skoglund and Aspenberg, 2007, Wang et al, 2007, Garrett et al, 2007.…”
Section: Study I: Statinssupporting
confidence: 74%
“…Consequently, studies on topical application of statins have been performed. These studies are consistent and report likewise improved fracture healing in rodents treated with statins topically (Skoglund and Aspenberg, 2007, Wang et al, 2007, Garrett et al, 2007.…”
Section: Study I: Statinssupporting
confidence: 74%
“…[37][38][39] Subcutaneous injection of simvastatin has no significant effect on bone formation, suggesting that circulating simvastatin levels might peak and then decrease rapidly. 23 These earlier reports indicated that systemic administration of simvastatin might not have the expected effect on bone formation. Accordingly, local administration was considered as a way to deliver simvastatin directly in therapeutic concentrations for bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have investigated local delivery of statins to increase bone healing and reported that statins have local beneficial effects. 5,[19][20][21][22][23][24][25][26] However, some studies showed adverse effects. 21,24,27 Thylin et al and Stein et al reported that local application of simvastatin 2.2 mg caused inflammation in soft tissue in a rat calvarial bone defect model and in mandible bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, systemic administration of statins for bone formation requires a much more higher dose than for lowering cholesterol, and safety has not yet been clearly reported [29,30]. On the other hand, local administration can be performed with smaller doses, but it requires multiple or continuous injections [31]. In response to this drawback, local application of low-dose statin with a slow-release drug-delivery system has been suggested [32,33].…”
Section: Discussionmentioning
confidence: 99%